A new era of HIV care for age-associated multimorbidity. Issue 1 (9th February 2023) - Collini, Paul; Mawson, Rebecca L.
Abstract : Purpose of review: The management of people with HIV has shifted focus from acute AIDS-defining illness towards improving detection of chronic disease and reducing impact of multimorbidity. In this review, we explore this shifting paradigm of HIV care and the evidence for alternative models proposed to provide integrated holistic services for people with HIV (PWH) with multimorbidity. Recent findings: Despite 25 years of the antiretroviral treatment (ART) era an increased incidence of noncommunicable disease (NCD) and multimorbidity in PWH persists. As the world moves closer to universal ART coverage this phenomenon is now reported in low- and middle-income settings. Multimorbidity affects PWH disproportionately compared to the general population and results in reduced health related quality of life (HRQoL), greater hospitalization and higher mortality. There is evidence that NCD care provision and outcomes may be inferior for PWH than their HIV negative counterparts. Various models of integrated multimorbidity care have developed and are grouped into four categories; HIV specialist clinics incorporating NCD care, primary care services incorporating HIV care, community NCD clinics offering integrated HIV care, and multidisciplinary care integrated with HIV in secondary care. Evidence is limited as to the best way to provide multimorbidity care for PWH. Summary: A new era of HIV care for an ageing population with multimorbidity brings challenges for health providers who need to develop holistic patient focused services which span a range of coexisting conditions.